INCREASING THE EFFICIENCY OF WORKING WITH SPHERIC DISCLE DEVICES ON IRRIGATED AREAS (Conference Zone, 2022)
Farmers widely use gear and disc harrows, chisel cultivators, graders and other levelers to prepare the land for spring sowing. In order to ensure quality preparation of lands for sowing at the level of agro-technical requirements, it is important to adjust the machines and use the units based on them.